Pengaruh Google Maps Sebagai Media Promosi Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Umkm Disablonin Sidoarjo - Setiawan, Yoyada; Dwi Nugroho, Agung; Ayu Sanggarwati, Diah (CV. Multi Kreasi Media, 2024)
This study aims to determine the effect of Google Maps as a promotional media and product quality on purchasing decisions for MSME products Disablonin Sidoarjo. The type of research applied is explanatory research with a quantitative approach method. The population in this study are consumers of Disablonin and the sample used was 96 respondents. The sampling technique used is purposive sampling. The data collection technique is primary data through questionnaires distributed via link Google Form. Data analysis in this study used multiple linear regression analysis, all tests were carried out using tools SPSS 25.0. From the results of the F test it is known that the significant value is 0.000 which is smaller than the value alpha 5% or 0.05 then Ho is rejected and Ha is accepted. With this it can be concluded that Google Maps as a promotional media (X1) and product quality (X2) simultaneously influence purchasing decisions (Y).